ANALISIS ANTESEDEN LOYALITAS PELANGGAN: PERAN KOMPLAIN DAN KEPUASAN PELANGGAN TELKOM FLEXI-TRENDY DI SURAKARTA - Karsono , (Universitas Trisakti, 2008)
The purpose of research is the role of customer satisfaction, complaint, trust switching cost and corporate image of the effect to customer loyalty.Data was obtained from 200 customer CDMA phone users TelkomFlexy-Trendy Card (PT Telkom) in Surakarta. The data was analyzed by Structural Equation Modelling (SEM).The result is complaint is negative significantly influence to customer satisfaction and corporate image. Customer satisfaction is significantly influence to trust, switching cost and corporate image. Trust, switching cost and corporate image is signicantly influence to customer loyalty. But customer satisfaction is not significantly influence to customer loyalty.Keywords: Customer loyalty, Complaint, Customer satisfaction, Trust, Switching cost, Corporate image.